2016
DOI: 10.17795/jjhr-39039
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Bleaching Treatments Effect on Micro Hardness of Four Different Aged Composites

Abstract: Background: In this study, four different types of composite samples were aged then exposed to 16% carbamide peroxide and 40% hydrogen peroxide, and the results were compared to a control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The resin matrix of the Valux Plus product contains Bisphenol A Diglycidyl Ether Dimethacrylate (BISGMA), Triethylene Glycol Dimethacrylate (TEGDMA) and silane treated ceramic, which are considered vulnerable to staining due to their increased hydrophilicity [20,21]. These composites have zirconia/silica fillers [22,23], which may have a porosity that facilitates colourant penetration. These results are in agreement with previous studies that have reported that products that contain similar components in the matrix and fillers, as in Valux Plus, were prone to staining and discolouration [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resin matrix of the Valux Plus product contains Bisphenol A Diglycidyl Ether Dimethacrylate (BISGMA), Triethylene Glycol Dimethacrylate (TEGDMA) and silane treated ceramic, which are considered vulnerable to staining due to their increased hydrophilicity [20,21]. These composites have zirconia/silica fillers [22,23], which may have a porosity that facilitates colourant penetration. These results are in agreement with previous studies that have reported that products that contain similar components in the matrix and fillers, as in Valux Plus, were prone to staining and discolouration [8].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the filler fraction for Gradia Direct is 73% by weight (64% by volume), containing silica and pre-polymerized fillers (average particle size 0.85 µm), and for Valux-Plus, it is 85% by weight (66% by volume), containing zirconiasilica fillers (particle size 0.6-1 µm) [22,23]. In this study, microhardness values for Gradia Direct samples were found to be significantly lower than for Valux Plus samples.…”
Section: Discussionmentioning
confidence: 99%
“…Microhardness is indicated by the resistance of a surface to penetration or permanent indentation. Microhardness is critical to the wear rate and clinical repair durability [ 41 ]. Surface hardness directly affects a material’s ductility, elasticity, toughness, and visco-elasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Micro-filled composite materials with particles of pre-polymerized organic filler and a high proportion of organic constituents are exceptions [ 22 ]. Pre-polymerized organic fillers have lower hardness than silica fillers and contain an organic component [ 41 ]. Therefore, in the current study, the reduction in the microhardness values could be mainly associated with an increase in the concentration of organic XL-BisGMA particles because of the organic nature of the filler [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation